2018
DOI: 10.5530/ijopp.10.4.50
|View full text |Cite
|
Sign up to set email alerts
|

The Current Scenario of Clinical Pharmacy Service in the Management of Patients with Diabetes Mellitus and Related Complications: Review Article

Abstract: Diabetes Mellitus (DM) is a group of metabolic disorder characterized by defect in insulin secretion, insulin action or both. The prevalence of diabetes continues to rise worldwide, placed in an increasing burden on healthcare systems and for the individual payers. This review is aimed to organize and examines the contribution of pharmacist in people living with diabetes mellitus and reviewed to whether the extent of diabetes management interventions delivered by pharmacist is successful in achieving the goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Diabetes care is complex and requires multidisciplinary medical care plus patient self-management and education [ 19 , 20 ]. Improved adherence levels may improve overall health care resource utilization and costs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes care is complex and requires multidisciplinary medical care plus patient self-management and education [ 19 , 20 ]. Improved adherence levels may improve overall health care resource utilization and costs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, integrating the clinical pharmacists into a health care team had shown to be effective in improving the outcomes in diabetic patients. (Demoz, 2018) ( Warrington,2012). The results of our study are most similar to a study by Abuloha S. (2016); and Katherine Fukunaga, 2020 which showed that a clinical pharmacist has a role in monitoring diabetic patients and decreasing HbAC however their study focused on the role of clinical pharmacist in Insulin management in an out-patient setting.…”
Section: Discussionmentioning
confidence: 99%